Effectiveness of forward freight agreements in mitigating handymax bulk ship-owners’ business risks between 2006 and 2015 - Chow, Lai Wan (2017)
Shipowners are constantly exposed to risks while operating in a volatile freight market, which determines the ability for shipowners to cover their cost obligations. In order to reduce their risk exposure, shipowners have to employ various risk management tools. Traditional physical hedging tools, such as the Time Charters (TC), have been utilized by shipowners to hedge their earnings in the freight market. Recently, the paper hedging tool, Forward Freight Agreement (FFA), was introduced as an alternative hedging tool to manage freight volatility and mitigate freight-rate risk. This paper aims to evaluate the effectiveness of using FFA as a hedging tool to mitigate shipowners’ business risk in the Handymax dry bulk market, from 2006 to 2015.